Analisis Adaptasi Karyawan Dalam Meningkatkan Produktivitas Dengan Metode Skala Likert Pada Dinas Tata Ruang Kota Bekasi - Yudiana, Eka Mega Putri; Syarif, Mahmud; Anggarini, Desy Tri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In a dynamic business environment, employee adaptation is crucial for organizational productivity. This study analyzes the role of employee adaptation in improving productivity within the Spatial Control Division of the Bekasi City Spatial Planning Office. Using a non-statistical quantitative approach, data was collected through direct observation of 45 employees and a Likert scale questionnaire. Descriptive analysis was performed by integrating findings from both observation and the questionnaire to identify the relationship between variables. The results demonstrate that adaptation to changes, such as the introduction of a new Canon printer, has a tangible impact on productivity. This is evidenced by observational data showing the time required to print a map decreased from 15 minutes to 8 minutes and the frequency of printing errors dropped from 10% to 2%. These findings align with the positive perceptions of employees recorded in the questionnaire. The validity and reliability of the instruments were also confirmed, with a Cronbach's Alpha of 0.895 for the adaptation variable (X) and 0.867 for the productivity variable (Y). The conclusion of this research confirms a positive correlation between adaptation and increased work productivity, highlighting that investing in the development of employee adaptability is a vital strategy for any organization.